In totum deparaffinization of biological samples and re-embedded in historesin for better diagnostic - Mazzoni, Talita Sarah [UNESP]; Quagio-Grassiotto, Irani [UNESP] (Wiley, 2021)
Paraffin has been the most traditional embedding medium used in histological techniques, however it can cause several technical artifacts. On the other hand, the use of plastic resins gives a more consistent and precise support to the tissues, allowing a better perfection of the histological sections. Thus, in an attempt to retrieve samples previously embedded in paraffin, we have described this new protocol which allows the material to be deparaffinized and re-embedded into historesin (glycol methacrylate). Paraffin embedded biological materials (en bloc) were deparaffinized and re-embedded with historesin. The histological sections of the samples (in paraffin and historesin) were analyzed under light microscope and the quality of the material was compared. As expected, samples embedded in historesin showed a better quality in their morphology, even if they were previously embedded in paraffin. Therefore, this new technique proposed here allows the recovery of old materials, through reprocessing to historesin, ensuring that materials already collected that cannot be obtained again are analyzed with greater clarity and great detail.
Keywords: cytochemistry; embedding medium; glycol methacrylate; histology; paraffin